(untitled) (Journal of Engineering, 2012)
This paper presents the study and analysis, analytically and numerical of circular cylindrical shell pipe model, under variable loads, transmit fluid at the high velocity state (fresh water). The analytical analysis depended on the energy observation principle (Hamilton Principle), where divided all energy in the model to three parts , strain energy, kinetic energy and transmitted energy between flow and solid (kinetic to potential energy). Also derive all important equations for this state and approach to final equation of motion, free and force vibration also derived. the relations between the displacement of model function of velocity of flow, length of model, pipe thickness, density of flowed with location coordinate x-axis and angle are derived. In numerical analysis the models are created by using ANSYS Workpench-12 program, where build two models one for fluid, and another for pipe (solid). Depended on CFX-ANSYS package, can transfer all parameters in the fluid (temp., presser, energy) to solid model. The result show a good agreement and low of percentage error between the analytically and numerical result. Also shows the effects of length and flow velocity on the behaviour of pipe